2010
DOI: 10.1177/0095798409355796
|View full text |Cite
|
Sign up to set email alerts
|

Family Matters: The Role of Mental Health Stigma and Social Support on Depressive Symptoms and Subsequent Help Seeking Among African American Boys

Abstract: African American adolescent boys underutilize mental health service due to stigma associated with depression. Gaining an increased understanding of how depressed, African American adolescent boys perceive their mental health needs and engage in help-seeking behaviors might play an essential role in efforts to improve their symptoms and access to care. Using a mixed-methods design, this study examined the influence of mental health stigma and social support on depressive symptoms among African American adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
183
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 55 publications
12
183
3
Order By: Relevance
“…Research has shown that African Americans' social network members play a vital role in their mental health and well-being. Strong social networks, in which African Americans have high social support and high social connectedness, are observed to be a protective factor against depressive symptoms in African Americans (Lincoln et al 2005;Lindsey et al 2010;Marshall and Rue 2012).…”
Section: Social Network Social Support and African American Mentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that African Americans' social network members play a vital role in their mental health and well-being. Strong social networks, in which African Americans have high social support and high social connectedness, are observed to be a protective factor against depressive symptoms in African Americans (Lincoln et al 2005;Lindsey et al 2010;Marshall and Rue 2012).…”
Section: Social Network Social Support and African American Mentalmentioning
confidence: 99%
“…From this perspective, one's social network provides guidance about behavioral norms. Previous research has shown that social network members can positively influence individuals' mental health behaviors, such as mental health help-seeking and coping (Lindsey et al 2010). …”
Section: Social Network and Healthmentioning
confidence: 99%
“…Particularly among young people, parental support continues to be the best predictor of affective disturbances (Zimmerman, Ramirez-Valles, Zapert, & Maton, 2000), and parental disapproval of mental health professionals is strongly associated with young people's avoidance of seeking help for mental illness (Chandra & Minkovitz, 2006;Lindsey, Joe & Nebbitt, 2010). With the transition to university, however, the importance of peer support may become more critical to help-seeking behaviors.…”
Section: Social Support and Help-seeking Stigmamentioning
confidence: 99%
“…With the transition to university, however, the importance of peer support may become more critical to help-seeking behaviors. This said, findings regarding the role of peer support have been inconsistent, with some research indicating a negative association between support from peers and depressive symptoms (Yang et al, 2010), while others have found a positive association between perceived support and stigma of help-seeking (as a result of a fear of losing face) (Lindsey et al, 2010), or no association between peer support and either depressive symptoms or stigma (Zimmerman et al, 2000). The effects of peer support might depend on characteristics of the specific source, including whether the support was from the same or a different ethnic group (Schneider & Ward, 2003).…”
Section: Social Support and Help-seeking Stigmamentioning
confidence: 99%
“…Therefore, pre-service teachers maybe begin to seek help from personals outside of the practicum school. mental health (Leavey, Rothi, & Paul, 2011;Lindsey, Joe, & Nebbitt, 2010). However, help-seeking had also been used to investigate the social support of students from parents, peers, and teachers and to predict a host of emotional and behavioral adjustments (Malecki & Demaray, 2003;Wenz-Gross & Siperstein, 1998).…”
Section: Introductionmentioning
confidence: 99%